The Effect of A Play-Based Approach on Learning Outcomes of Basic Pencak Silat Movements Junior Athlete - Aisyatul Fitri; Weny Sasmitha; Suwirman Suwirman (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
This study aims to determine the effect of a play-based approach in Physical Education, Sports, and Health (PJOK) learning on pencak silat material toward students’ learning outcomes. The research method used was an experimental design involving an experimental group and a control group. The research sample consisted of 21 students in the experimental class and 21 students in the control class. The data were analyzed using prerequisite tests (normality and homogeneity) and hypothesis testing using the Pearson Product Moment correlation test. The results showed that the mean score of the control variable was 86.81, while the mean score of the experimental variable was 93.33. Based on the correlation test, the obtained value was r = 0.385, indicating a positive relationship at a low level of correlation. However, the significance test results showed that t-count (1.81) < t-table (2.093).